Effect of Calcination Temperature on Performance of Photocatalytic Reactor System for Seawater Pretreatment - Weerana Eh Kan; Jamil Roslan; Ruzinah Isha (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
Conservative desalination technology including distillation requires high energy and cost to operate. Hence, pretreatment process can be done prior to desalination to overcome energy demand and cost reduction. Objective of this research is to study the effect of calcination temperature of hybrid catalyst in photocatalytic reactor system in the seawater desalination, i.e. salt removal in the seawater. The catalyst was synthesized via wet impregnation method with 1:1 weight ratio of TiO2 and activated oil palm fiber ash (Ti:Ash). The catalyst was calcined at different temperature, i.e. 500 oC and 800 oC. The study was carried out in a one liter Borosilicate photoreactor equipped with mercury light of 365 nanometers for two hours with 400 rpm mixing and catalyst to seawater sample weight ratio of 1:400. The Chemical Oxygen Demand (COD), pH, dissolved oxygen (DO), turbidity and conductivity of the seawater were analyzed prior and after the testing. The fresh and spent catalysts were characterized via X-Ray Diffractogram (XRD and Nitrogen physisorption analysis. The calcination temperature significantly influenced the adsorption behaviour and photocatalytic activity. However, Ti:Ash which calcined at 800 oC has less photocatalytic activity. It might be because the surface of fiber ash was sintered after calcined at high temperature. The Ti:Ash catalyst that calcined at 500 oC was found to be the most effective catalyst in the desalination of seawater by reducing the salt concentration of more than 9 % compared to Ti:Ash calcined at 800 oC. It can be concluded that catalyst calcination at 500 °C has better character, performance and economically feasible catalyst for seawater desalination.